Parameters of the In-Run Position of Juniors' Body at the Beginning of Take-Off - Andriy Kazmiruk; Volodymyr Banakh; Andriy Vlasov; Anatolij Lopatiev; Oleksandr Tovstonoh; Natalia Stefanyshyn (OVS LLC, 2017)
The objective is to determine the differences in the technique of the in-run position execution at the beginning of take-off by junior ski-jumpers of different qualification (sports training). Materials and methods. The participants in the study were 22 junior ski-jumpers aged 14-16 (a group of junior ski-jumpers) performing during the Ukrainian Ski-Jumping Championship (October 9, 2010, Vorokhta, Ukraine). The correlation analysis thereof established the relations between the jump length and the angular parameters: in the ankle joint, knee joint, hip joint, and pelvis joint, which condition the positional relationship of the body joints and the position of the ski-jumper at the beginningof take-off.  Results. The study established the correlation relations between the jump length and the angular parameters that condition the horizontal positioning of the body. The correlation coefficient for the jump length at the inclination angle of the segment of the straigt line passing through the axes of the ankle and shoulder joints to the direction of the skier's movement is r=-0.563 (p = 0.006), and that at the inclination angle of the segment of the straight line passing through the general center of body weight and the axis of the ankle joint to the direction of the skier's movement is r= -0.355 (p = 0.105). Conclusions. A position of lowly groupping at the beginning of the take-off allows to improve the sporting result. The study established the correlation between the jump length and the angle, particularly in the ankle joint, to be r= -0.2244 (p = 0.274), in the knee joint - r= -0.165 (p = 0.464), in the hip joint -r= -0.127 (p = 0.574). It determined the statistically reliable differences in the parameters of the body position at the beginning of the take-off on the jump ramp (p <0.05).